Enhanced solar light driven activity of p-n heterojunction for water oxidation induced by deposition of Cu2O on Bi2O3 microplates - Ke, J.; Zhao, C.; Zhou, H.; Duan, Xiaoguang; Wang, Shaobin (Elsevier, 2019)
As an important half reaction in solar-driven water splitting, it is more challenging to develop low-cost and highly efficient photocatalysts for water oxidation. The enhancement of sunlight harvesting and inhibition of charge-carrier recombination are keys to fabricating efficient semiconductor-based photocatalysts for energy conversion from solar light to chemicals. Herein, we reported highly dispersive Cu2O/Bi2O3 composites prepared by a facile and benign synthetic route, where n-type Bi2O3 microplates and nano-sized p-type Cu2O were coupled together to construct heterojunctions to improve the transportation efficiency of photoinduced charge carriers, benefited from the intimate interactions at the interfaces between Bi2O3 and Cu2O. The electrochemical properties of charge-transportation and population of charge carriers were investigated in the heterojunctions. The hybrid materials exhibit both enhanced photocatalytic performances in water oxidation and photodegradation of dyes compared with sole Bi2O3 or Cu2O under artificial solar light irradiation. The initial O2 evolution rate of the heterojunction system is 1.4- and 8-fold higher than the pure Bi2O3 and Cu2O, respectively. This study provides new protocols for synthesizing novel hybrid materials with insights into heterojunction-based photocatalysis for green energy production and wastewater purification.